METHODS OF INTRODUCING INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN EDUCATION - Abdusamadov Zafar; Alisherova Dilshoda Azizxon qizi (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article discusses innovative pedagogical technologies and their effective, step-by-step use in education, the importance of pedagogical technologies in the educational process.